USE OF LANDSAT IMAGERY TO MAP SPREAD OF THE INVASIVE ALIEN SPECIES Acacia nilotica IN BALURAN NATIONAL PARK, INDONESIA - Sutomo Sutomo; Eddie van Etten; Rajif Iryadi (SEAMEO BIOTROP, 2020)
In the late 1960s, Acacia nilotica was introduced to Baluran National Park to establish fire breaks which would prevent the spread of fire from Baluran Savanna to the adjacent teak forest. However, A. nilotica has spread rapidly and has threatened the existence of Baluran Savanna as it has caused an ecosystem transition from an open savanna to a closed canopy of A. nilotica in some areas. This study is one of the few that examines A. nilotica invasion in Baluran National Park through remote sensing. Land cover dynamics were quantified using a supervised classification approach on Landsat 7 and 8 multi-spectral images. Results showed that savanna and A. nilotica can be recognized using a composite of bands 6, 5 and 3 of the Landsat 8 image. Across a 14-year period (2000-14), A. nilotica has spread far north and south from its originally introduced location, invading not only savannas but also dry forests in the Baluran National Park. The savanna size has decreased by 1,361 ha, meanwhile the A. nilotica stand has increased by 1,886 ha over this period. Spatial distribution of A. nilotica in Baluran National Park showed a clumped pattern. Acacia nilotica which develops into a homogeneous stand in the north-west and eastern parts of the national park occupied an area of 3,628 ha or about 14.5% of the total area. This study has demonstrated that remote sensing technology can be effectively used to estimate the patterns of distribution and amount of A. nilotica cover change over the whole Baluran National Park. This is one advantage of remote sensing and GIS, as it is difficult and expensive to make such direct assessments using the conventional approach of field survey and vegetation analysis.